Integration of public health with adaptation to climate change lessons learned and new directions - Ebi, Kristie L.; Smith, Joel B.; Burton, Ian (Taylor & Francis, 2005)
Overall, the negative health impacts of global climate change are anticipated to significantly outweigh positive impacts. Furthermore, global climate change will continue for decades, even after the effective implementation of mitigation measures. By exploring cases in public health and prior lessons learned, this valuable title identifies the key adjustments necessary for public health systems to effectively adapt to this inevitable climate change. Touching on broader aspects of integrated assessment and environmental studies as well as climatic alterations and public health, this book is an essential resource for those involved in these fields at all levels.
Keywords: Climatic changes -- Health aspects.; Environmental health.; Medical policy.; Medical climatology.; elektronické knihy; electronic books